Cognitive and Linguistic Benefits of Aerobic Exercise: A State-of-the-Art Systematic Review of the Stroke Literature - Mayer, Jamie F.; Sandberg, Chaleece W.; Mozeiko, Jennifer; Madden, Elizabeth B.; Murray, Laura L. (Frontiers in Rehabilitation Sciences, 2021)
This systematic review aimed to determine how aerobic exercise affects cognition after stroke, with particular focus on aphasia and language improvement. Methodological quality was assessed with the PEDro+ scale with half of the 27 included studies rated as high quality. Data extraction focused on cognitive effects of aerobic exercise post-stroke, intervention characteristics, outcome measures, and participant characteristics. Whereas attention, memory, and executive functioning measures were common across the included studies, no study included a language-specific, performance-based measure. Seventeen studies reported positive cognitive effects, most frequently in the domains of attention, memory and executive functioning. Variability in outcome measures, intervention characteristics, and participant characteristics made it difficult to identify similarities among studies reporting positive cognitive effects of exercise or among those studies reporting null outcomes. Only three studies provided specific information about the number of individuals with aphasia included or excluded, who comprise approximately one-third of the stroke population. The review identified patent gaps in our understanding of how aerobic exercise may affect not only the cognitive domain of language post-stroke but also the broader cognitive functioning of individuals with post-stroke aphasia. Methodological limitations of the reviewed studies also warrant further examination of the direct impact of aerobic exercise on cognition post-stroke with careful attention to the selection and reporting of population, intervention, and outcomes.